Methodological proposal for the measurement of the plebiscitary electoral democracy index based on the Varieties of Democracy Project - Paredes Encalada , Ana Marcela (2023)
This paper proposes that the index of participatory components of direct democracy be included in the Varieties of Democracy (V-Dem) project to measure plebiscitary electoral democracy. In the V-Dem project, half of the measurement correspond to the additive polyarchy index and the other half to five indices: fair elections, freedom of expression, association, multiplicative polyarchy and percentage of the population with suffrage. This study proposes the concept, attributes, and components of a sixth element: the index of participatory components. Arguably, including assessments of direct democracy exercises (plebiscite, referendum) would allow electoral democracy to be revalued. Considering that the elections variable is the cornerstone of any representative democracy, this proposal could provide a reliable, neutral, and impartial methodology.